Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1002/j.1460-2075.1990.tb08162.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Ca2+ oscillations evoked by receptor stimulation, G-protein activation, internal application of inositol trisphosphate or Ca2+: simultaneous microfluorimetry and Ca2+ dependent Cl- current recording in single pancreatic acinar cells.

Abstract: The effects of acetylcholine (ACh), cholecystokinin (CCK), internally applied GTP‐gamma‐S, inositol trisphosphate [Ins (1,4,5) P3] or Ca2+ on the cytoplasmic free Ca2+ concentration [( Ca2+]i) were assessed by simultaneous microfluorimetry (fura‐2) and measurement of the Ca2(+)‐dependent Cl‐ current (patch‐clamp whole‐cell recording) in single internally perfused mouse pancreatic acinar cells. ACh (0.1‐0.2 microM) evoked an oscillating increase in [Ca2+]i measured in the cell as a whole (microfluorimetry) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
209
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(230 citation statements)
references
References 62 publications
18
209
2
Order By: Relevance
“…The ion channels that carry these currents are both Ca# + -activated [21,22]. Whole-cell currents in exocrine acinar cells are used routinely to assess changes in cytosolic free Ca# + activity ([Ca# + ] i ), and they have been shown to reflect accurately changes in [Ca# + ] i [23]. In contrast with studies using pancreatic [23], submandibular [24] or parotid [25] acinar cells, we have been previously unable to demonstrate oscillatory changes in Ca# + -dependent currents in response to ACh in freshly isolated lacrimal acinar cells ( Figure 1A ; typical of 36 observations.)…”
Section: Resultsmentioning
confidence: 99%
“…The ion channels that carry these currents are both Ca# + -activated [21,22]. Whole-cell currents in exocrine acinar cells are used routinely to assess changes in cytosolic free Ca# + activity ([Ca# + ] i ), and they have been shown to reflect accurately changes in [Ca# + ] i [23]. In contrast with studies using pancreatic [23], submandibular [24] or parotid [25] acinar cells, we have been previously unable to demonstrate oscillatory changes in Ca# + -dependent currents in response to ACh in freshly isolated lacrimal acinar cells ( Figure 1A ; typical of 36 observations.)…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that, in addition to the InsP3-sensitive store, these cells also possess a caffeinesensitive Ca 2÷ store that is diffusely distributed throughout the cell [5]. Caffeine-sensitive Ca 2÷ stores have also been identified in smooth muscle cells [6,7], sympathetic [8,9] and sensory [10] neurons, pancreatic acinar cells [17] and rat chromaffin cells [11]. The role that InsP3-insensitive stores play in Ca 2+ signalling in cells is unknown but is the subject of intense speculation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The role that InsP3-insensitive stores play in Ca 2+ signalling in cells is unknown but is the subject of intense speculation (e.g. [8][9][10][11][12][13][14][15][16][17]). …”
Section: Introductionmentioning
confidence: 99%
“…Amylase Secretion Assay from Pancreatic Acini-Pancreatic acini were prepared as described with some modifications (27). Briefly, chopped pancreases of mice were digested with digestion buffer (KR buffer, pH 7.4, 10 unit/ml collagenase type IV (Sigma-Aldrich), 1% (w/v) BSA) and washed with KR buffer, 1% (w/v) BSA.…”
Section: Methodsmentioning
confidence: 99%